Les cafés, reflets de la diversité des tiers-lieux contemporains : aperçu de Montréal - Sandra Breux; Mario Bédard (Netcom)
The emergence of new forms of cafés (café-chat, café-friperie, etc.) raises the question of the impact of this type of business on the daily lives of some workers, inhabitants and, more broadly, on the territory where they are located. Often presented as the archetype of the third place, the recent evolution of the café questions the relevance of this designation, even though its relationship to the territory and its identity are often neglected. Based on the analysis of some of Montreal’s cafés, this article proposes to reflect on the role of cafés as potential third places that allow for the affirmation of the characteristics of the neighborhood in which they are located, and the improvement of the milieu and quality of life of the workers and residents who frequent them or live nearby. If the success of these businesses seems to be based more on their distinction than on their location, the fact remains that they are not all third places to the same degree, and their impacts on workers and residents also vary according to nature and scope of their territorial anchorage. The spectrum of the spectrum of this territorial anchoring allows us to enrich and nuance the usual definition of third places.